Study Of Translation Techniques In "Forest Of The Thousand Demon" By Mashood Jimba/ Ø£Ø³Ø§Ù„ÙŠØ¨ Ø§Ù„ØªØ±Ø¬Ù…Ø© ÙÙŠ Ø§Ù„Ø±ÙˆØ§ÙŠØ© Ø§Ù„ÙŠÙˆØ±Ø¨Ø§ÙˆÙŠØ© Ù„Ù…ØªØ±Ø¬Ù…Ø© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© "Ø§Ù„ØµÙŠØ§Ø¯ Ø§Ù„Ø¬Ø±ÙŠØ¡ ÙÙŠ ØºØ§Ø¨Ø© Ø§Ù„Ø¹ÙØ§Ø±ÙŠØª" Ù„Ù…Ø´Ù‡ÙˆØ¯ Ø¬Ù…Ø¨Ø§ Ø§Ù†Ù…ÙˆØ°Ø¬Ø§ - Adebisi, Aliy Abdulwahid; Abubakar-Hamid, Hasanat Funmilayo (Ijaz Arabi Journal of Arabic Learning, 2020)
The Nigerian Nation has witnessed a multifaceted development in various field of knowledge; Translation studies is not an exemption. The Translation scholars' contributions in the applied translation are highly commendable, though, at the expense of the field of translation studies. They (Nigerian scholars) have shown much academic prowess in translating from Indigenous languages into foreign languages and vice versa to showcase Nigerian heritage in cultures, values, and enjoyable characters. Some engage in scientific translation while another group is dealing with the genre of literary translation. The present research is an appraisal of D.O. Fagunwa's novel " Ogboju ode in Igbo Irunmale" translated by a translation scholar Mashood Mahmud Muhammad Jimba. Using a contrastive survey analytical method in showing manners of equivalence in translation within the selected samples, the work focused mainly on the procedures established by Vinay and Darbelnet for translation from and into another language. The method employed pointed out aspects of a suitable translation procedure, the results of which replicate the same situation as in the original demonstrated by the author of the texts analyzed. The study thus appraises the scholar's work objectively